Optimization of Deep Foundation Design in a Sand, Gravel and Cobble Formation - Using Pressuremeter Testing In Slotted Sleeve Casing (8ff70823-b892-4925-865f-fae636443d0f) - Emad Farouz; Roger Failmezger (Deep Foundations Institute, 2007)
"The proposed reconstruction of I-75 downtown consists of widening an approximately 2.46 Km section of IR-75 through the northern section of downtown Dayton, OH, USA. Bridge B-13 is a 9-span continuos prestressed concrete I-beam, 319.0-meter (1,048-foot) long bridge with a stub abutment on MSE walls for the rear abutment, and a stub abutment with spill-through slopes for the forward abutment. The piers in the river were located parallel to the Great Miami River, and are full-height reinforced concrete walls. PRESSUREMETER TEST PROCEDUREThe driller advanced either casing or augers approximately 1 meter above the pressuremeter test. Steel casing was used to advance borings performed in the river, and augers were used for borings on land. Mud rotary drilling with a large diameter roller bit was used to remove all of the gravel and cobble fragments inside the casing or augers.At the pressuremeter test elevation the driller used a 63.5-mm (2.5-inch) carbide button bi-cone bit, using a rotation rate of about 60 rpm, a mud fl ow rate of about 10 gallons per minute (40 liters per minute), and an advance rate of 6 to 10 minutes per meter (2 to 3 minutes per foot). To minimize vibrations, advance rates were slower where excessive cobbles were encountered. The 63.5-mm (2.5-inch) O.D. slotted casing pressuremeter was lowered to the test elevation, often requiring either pushing or hammering into the test zone. We believe that the test zone was not perfectly straight, or that gravel or cobble fragments jutted into the test zone and had to be displaced to advance the pressuremeter into the test zone. The slotted casing prevented membrane damage during insertion. A photograph of the slotted casing being lowered into the borehole is shown below.The pressuremeter was calibrated for system compressibility and membrane resistance. At full expansion of 800 cm3, the membrane resistance of the slotted casing was about 2.5 bars.Strain-controlled tests were performed using a Texam control unit with a monocell probe. Volume increments of 20 cm3 were injected into the probe and corresponding pressures were measured. Near the end of the elastic portion of the test, an unload-reload cycle was done. A creep test was performed for 10 minutes at the next volume increment. The test continued until either 800 cm3 were injected or the membrane burst."